PENGARUH IKLIM ORGANISASI, FLEKSIBILITAS KERJA, DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN PERUSAHAAN STARTUP (STUDI KASUS PADA PT XYZ) - Tiara Adelia (2022)
This research is using quantitative study aimed to see whether there are influence of organizational climate, work flexibility, and employee engagement on employee performance. This study uses employee at one of startup company in Indonesia, which is PT XYZ. The sample used was 37 respondents, with the sampling technique using purposive sampling. In this research hypothesis, namely to know the effect either partially or simultaneously of variables independent and dependent variable, so the tests used are the coefficient of determination test, t-test and f-test. From the test results obtained: (1) Organizational Cimate has a positive and significant effect on employee performance (2) Work flexibility has a positive and significant effect on employee performance (3) Employee Engagement has a positive and significant effect on employee performance (4) Organizational climate, work flexibility, and employee engagement have a simultaneous effect on employee performance.